Clinical outcome of salvage neck dissections in head and neck cancer in relation to initial treatment, extent of surgery and patient factors. (24th January 2017) - van den Bovenkamp, K.; Noordhuis, M.G.; Oosting, S.F.; van der Laan, B.F.A.M.; Roodenburg, J.L.; Bijl, H.P.; Halmos, G.B.; Plaat, B.E.C.
Abstract : Objective: Salvage surgery has a higher complication rate compared to primary surgical treatment. We evaluated clinical outcome of salvage neck dissections in relation to initial treatment modality, extent of surgery and patient‐related factors. Design: Single institution consecutive case series. Setting: Tertiary Head and Neck Cancer Centre. Participants: In all, 87 patients with head and neck squamous cell carcinoma, who underwent salvage neck dissection after initial radiotherapy ( n = 30), radiotherapy with carboplatin/5‐fluorouracil ( n = 43) or radiotherapy with cetuximab ( n = 14). Main outcome measures: Incidence of complications, disease‐specific survival. Results: Complications occurred in 28% of the patients. Multivariate analysis identified extent of neck dissection as the only independent predictor of surgical complications ( P = 0.010). Surgical complication rate was 16% after radiotherapy with systemic treatment, and 47% after radiotherapy alone ( P = 0.171). The 5‐year disease‐specific survival was 55%, independent of complications, initial treatment, extent of surgery and patient‐related factors. Conclusion: The only predictor for surgical complications was extent of surgery. Survival was not influenced by complications.